Features of Pragmatism in Educational Theater Performances - Attallah Al-Kubaisi, Iman Abdul Sattar (Journal of Tikrit University for Humanities, 2023)
The inquiry on the key characteristics of pragmatism in educational theatre performances necessitates an academic approach. Establish two research objectives: Pragmatism is a philosophical perspective that emphasizes the practical consequences and utility of ideas and actions. It posits that the value of any belief or theory lies in its ability to produce desirable outcomes and solve real-world problems. Educational theatre, as a medium of instruction and artistic expression, effectively teaches pragmatism by integrating practical experiences and active learning into the educational processThe primary emphasis of this research is the pragmatic-based instructional theatre in Iraq from 2010 to 2020. In the first chapter, the search criteria including characteristics, pragmatism, and educational theatre were established. Subsequently, the second chapter elucidated the principles of pragmatic thinking, educational theatre, and the interrelationship between these two concepts, as of the year 2021. The third phase of the study included a comprehensive analysis of the Iraqi educational theatre landscape, spanning from 2010 to 2021. This investigation involved the examination of 20 distinct performances within the research community, including both descriptive and analytical methodologies. The Princess of Dreams was selected at random. The next paragraphs show the results of the study. Paragraph 1: The study examined the relationship between exercise and mental health in a sample of 200 participants. The The variable had the highest weighted mean of 3 and a relative weight of 100%. The proportion of her educational play appearances is comparatively greater. The individual achieved a weighted mean score of 94.44, indicating a commendable performance that positions them as the runner-up in the Princess of Dreams competition. The weighted mean of the variable is 2, with a relative weight of 66.67. The researcher emphasized the need of implementing the study's results within the realm of theatrical school activities, since educational theatre has been shown to significantly contribute to students' overall well-being and success.